PENGARUH EKSTERIOR DAN GENERAL INTERIOR TERHADAP PERILAKU PEMBELIAN DI SUPER INDO SINGOSARI MALANG - Joni Dwi Pribadi; Erlangga Andi Sukma; Eko Boedhi Santoso (Adbis: Jurnal Administrasi dan Bisnis, 2017)
This research was intended to analyze the implementation,responses of customers, and to analyze how big the influence of exterior and general interior is on purchasing behavior. The kind of research is explanatory research with two independent variables which are exterior and general interior designand purchasing decision as the dependen variables, using data collection techniques of questionnaire, interviews, observation, documentation, with accidental sampling. The respondents of this research were 90 customers at Super Indo Singosari. The data were then analyzed with multiple regression analysis. The result showed that Y = 6,694 + 0,198 X1 + 0,382 X2. It mean that exterior design and general interior design had positive and significant effect on purchasing decision. The determination coefficient score was 0,465; it mean that variables (exterior and general interior) had 46% effect on purchasing decision, and the rest 54% was influenced by other variables such as price, product, quality, and others not included in this research.